(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT Praise be to God, Lord of the Worlds, and blessings and peace be upon the Master of the Messengers. As for after : We know that measurement is one of the broadest topics in theology. The illness is one of its most important issues. Therefore, we see that the scientists paid much attention to the illness , and what they paid more attention from the issues of the illness was the paths and methods of proving them in the origin, they investigated in its origin more than their investigation in its branch, because the letter could be ensured by any significant evidence. The research consisted of two topics, in the first - I dealt with the meaning of the title of the research in language and convention, and in the second - I spoke about the text’s formulas and expressions, and in the conclusion I summarized the most important research issues.